PROBLEM SOLVING HEURISTIC TO DEVELOP SCIENTIFIC REASONING - Wuriyudani, Hasri Arlin; Wiyanto, Wiyanto; Darsono, Teguh (Physics Communication, 2019)
Scientific reasoning patterns of students formal operational base on the implementation of problem solving heuristic methods has been obtained. The aim of this research is knowing the influence of heuristic problem solving method that has been designed on practicum sheet of discovery learning model to develop scientific reasoning of students. The samples are 32 students in junior high school at 11-13 years old. The methods are CTSR test of scientific reasoning by Lawson and interview. The research design is one grup pretest-posttest. The results indicated that problem solving heuristic methods can be a factor to develop scientific reasoning of students. The lowest level of scientific reasoning (concrete reasoning pattern) is decrease 34,38%. The middle level of scientific reasoning (transitional reasoning pattern) is increase 31,25%. The highest level of scientific reasoning (formal reasoning pattern) is increase 3,13%. Heuristic methods helping students to develop scientific skills, such as setting hypotheses, modifying variables, and analyzing results of research. The scientific reasoning pattern can not be classified by age. People who has older of age has not impact in high scientific reasoning level than younger people. If someone fail on concrete aspect, it is not necessarily that person will be fail in formal aspect.